Construction of nursing standard of integrated traditional Chinese and Western medicine for patients with COVID-19 (mild and common) in Beijing based on Delphi method - Jing Zhang; Xue-Ling Ma; Jian-Hua Deng; Jing Li; Zh-Yun Zhang; Ling Tang (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this study is to establish a nursing standard of integrated traditional Chinese and Western medicine for patients with COVID-19 (mild and common) in Beijing, to provide reference for clinical nursing of patients with COVID-19 (mild and common). Methods: Through online communication meeting with nurses who are in the frontline of anti-epidemic, clinical investigation, literature research, and expert demonstration meeting are carried out to prepare the draft of the standard, and the Delphi method is applied to determine the standard of integrated traditional Chinese and Western medicine care for patients with COVID-19 (mild and common) in Beijing. Results: The nursing standard of integrated traditional Chinese and Western medicine for patients with COVID-19 (mild and common) was established, which included 5 first-level indicators, 14 second-level indicators and 60 third-level indicators. After two rounds of Delphi method, the positive coefficients of experts were 96% and 83%, the authoritative coefficients of experts were 0.89 and 0.91, and the Kendall's coefficient of concordance (W) of experts were 0.12, 0.09, 0.10, 0.13 (P < 0.05) and 0.44, 0.43, 0.37, 0.39 (P < 0.05). Conclusion: The standard of integrated traditional Chinese and Western medicine nursing for patients with COVID-19 (mild and common) in Beijing constructed by the Delphi method is scientific and practical, which provides a reference for clinical application of integrated traditional Chinese and Western medicine nursing to fight against COVID-19 infection.